A ANALISIS FAKTOR-FAKTOR SATISFIERS PADA TINGKAT KEPUASAN SISWA DALAM PEMBELAJARAN OTOMOTIF - Purnawan Purnawan; Casnan; Heti Triwahyuni; Budi Santosa (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2021)
Herzberg's theory of job satisfaction is applied by automotive electrical learning in that the level of student satisfaction in learning automotive had influenced by two factors, namely satisfiers and dissatisfiers. This study aims to describe and analyze satisfiers factors on the satisfaction level of class XI students majoring in TKRO SMK Muhammadiyah 1 Moyudan in the 2019/2020 academic year in studying automotive electricity with a population size of 132 students. This study uses census research because all population units are affordable and possible to avoid data corruption. The variables studied were: satisfiers in learning automotive electricity included achievement of individual student achievements in automotive electrical lessons, self-recognition/actualization in automotive electrical learning, the automotive electrical study itself, self-responsibility to study automotive electricity, and self-potential development of students in studying automotive electrical engineering. The data collection tool used in this research is a questionnaire. The data collected were analyzed by descriptive technique. The results showed that student satisfaction in studying automotive electrical is achieved by satisfying factors